(untitled) (Al-Qamar, 2025)
The concept of human dignity occupies a central position in the Qur’anic worldview. Islam regards humanity as the most honored creation of Allah, endowed with reason, free will, and moral responsibility. This research paper critically examines the concept of Takrīm al-Insāniyyah (the dignity of humankind) through the interpretative insights of selected contemporary Qur’anic commentators. The study explores how modern exegetes such as Mufti Muhammad Taqi Usmani, Shabbir Ahmad Usmani, Naeem-ud-Deen Muradabadi , Hafiz Salahuddin Yusuf, and Dr.Sayyad Hamid Hasan Bilgrami have articulated the notion of human honor in relation to divine guidance, ethical conduct, and social justice. It also discusses the Qur’anic injunctions that emphasize the sanctity of human life, equality among people, and the universal principle of respect for all humans regardless of race, creed, or status. Furthermore, the research analyzes how contemporary challenges—such as human rights, social discrimination, and moral decline—are addressed within the framework of Qur’anic ethics. The purpose of this study is to bridge traditional exegetical understandings with modern socio-ethical realities, highlighting the timeless relevance of Qur’anic principles in preserving human dignity. The findings reveal that the preservation of human dignity is not merely a moral ideal but a foundational objective (maqṣad) of the Islamic Shariah, ensuring justice, compassion, and social harmony in human civilization.